Notas sobre gasteromicetes I: Tulostoma fimbriatum Fr. var. heterosporum J. E. Wright - Martín Esteban, María Paz (Revista Catalana de Micologia, 2007)
Notes on Gasteromycetes I: Tulostoma fimbriatum Fr. var. heterosporum J.E. Wright.M.P. Martín. Tulostoma fimbriatum var. heterosporum has been recorded for the first time in Spain. Its main character is to present in the madure gleba two types of spores. Notes on its macro, microscopical features are also given.